Studi Penentuan Difusivitas Panas Mangga Arummanis Terproses Minimal - Lamhot P Manalu; Amos Lukas; Gustri Yeni (Institution for Industrial Research and Standardization of Industry - Padang, 2012)
The important limitation in process design for agricultural products is the lack of information on their thermal properties. Although a lot of experimental data can be found, the variety of products and the differences in measurement method make limitation on the value of the available data, especially for Indonesian products. These data are required to get information about temperature change when product was processed like heating or cooling. It is worth to optimize efficiency of energy. The objective of this study was to predict thermal diffusivity and conductivity of minimmaly processed product of arummanis mangoes. The value was determined numerically with direct and indirect methods. The result showed that thermal conductivity was 0.6058 W/moC while thermal diffusivity was 1.70 x 10-7 m2/s (direct method).ABSTRAKPada perancangan suatu sistem pengolahan hasil pertanian diperlukan pengetahuantentang sifat-sifat panas suatu bahan diantaranya panas jenis, konduktivitas, dan difusivitas panas. Nilai-nilai tersebut untuk produk pertanian lokal sangat jarang ditemukan, sehingga dalam aplikasinya sering digunakan data sifat panas dari literatur luar yang belum tentu sesuai dan tepat dengan produk dalam negeri, hal ini dapat menyebabkan terjadinya bias dalam perhitungan dan perancangan. Studi ini bertujuan untuk menentukan sifat-sifat panas dari produk mangga arummanis terproses minimal. Hasil studi ini mendapatkan bahwa nilai panas konduktivitas panas mangga arummanis terproses minimal adalah 0.6058 W/moC, sedangkan nilai difusivitas panasnya adalah 1.70x10-7 m2/detik.